2017
DOI: 10.18488/journal.aefr.2017.75.528.540
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Culture Impact of Increasing Satisfaction and Performance of Employees: Study of Educational Institutions Sabillilah Sampang

Abstract: Article History JEL Classification J530.Many studies conducted by experts who want to know the direct relationship between organizational cultures with organizational performance, but there are also some empirical studies which found that organizational culture is directly does not have a significant impact on employee performance, which means other variables that directly affect the performance employees. Therefore, this study seeks to show how big the Islamic culture through job satisfaction influence on emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
1
2
0
2
Order By: Relevance
“…The results of the study are in line with what was stated by Purnama (2017) Organizational culture has a significant effect on work discipline of employees. Ting (2011) to create effective and efficient employee performance for organizational progress, it is necessary to have organizational culture as one of the work guidelines that can be used as a reference for employees to carry out organizational activities.…”
Section: The Effect Of Organizational Culture On Work Discipline Of E...supporting
confidence: 90%
See 1 more Smart Citation
“…The results of the study are in line with what was stated by Purnama (2017) Organizational culture has a significant effect on work discipline of employees. Ting (2011) to create effective and efficient employee performance for organizational progress, it is necessary to have organizational culture as one of the work guidelines that can be used as a reference for employees to carry out organizational activities.…”
Section: The Effect Of Organizational Culture On Work Discipline Of E...supporting
confidence: 90%
“…Purnama (2013) found that organizational culture has a strategic role in improving employee performance. In Purnama (2017) study found that organizational culture can increase satisfaction. Keller et al, (2004) defines organizational culture is a pattern of shared basic assumptions that the group learns as it is solved, problems of external adaptation and internal integration, that has worked well enough to be considered valid and, therefore, to be taught to new members as a matter of understanding, thinking and feeling in relation to those problems.…”
Section: Introductionmentioning
confidence: 97%
“…According to Purnama (2017), Islamic culture, which emphasizes competence, dedication, honesty, and transformation, can genuinely have an impact on employee job satisfaction and, in turn, employee performance, as evidenced by the quantity, quality, efficiency, and accuracy of the work that employees produce. In their study, Lumley et al (2011) examined the relationship between job satisfaction and nine variables, including pay, promotion, supervision, fringe benefits, recognition and reward, working conditions, coworkers, and work environment.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Kondisi ini di dukung penelitian yang dilakukan oleh (Falah et al, 2021) pada pesantren modern Ummul Quro Al-Islami Bogor menyatakan bahwa kejujuran dalam bekerja dengan menjalankan etika kerja dan etos kerja islami akan memperkuat komitmen organisasioal dan pada akhirnya berdampak pada pertumbuhan pesantren tersebut. Pernyataan itu sesuai dengan penelitian yang dilaksanakan sebelumnya oleh (Purnama, 2017) yang mana budaya islam (kompetensi, komitmen, kejujuran dan transformatif) akan menyebabkan peningkatan kinerja yang dimediasi oleh variabel kepuasan karyawan. Memilih seorang Supervisor atau pemimpin yang jujur dalam bekerja menjadi penting dalam kemajuan tumbuh kembang sebuah organisasi bisnis (Do et al, 2021).…”
Section: Nilai-nilai Islami Dalam Kewirausahaanunclassified
“…Hal tersebut mengidentiffikasikan bahwa kejujuran seorang pelaku bisnis memiliki dampak pada peningkatan kinerja bisnis. Penelitian ini sejalan dengan penelitian yang dilakukan oleh (Gomez-perez & Jourde, n.d.) dan (Purnama, 2017).…”
Section: Pengaruh Kejujuran Terhadap Kinerja Bisnisunclassified